Implementasi dan Analisis Algoritma FIFO, FEFO, dan LIFO pada Sistem Automated Storage and Retrieval System (ASRS) Berbasis Internet of Things untuk Produk Minuman Kemasan - Muhammad Daffa Fauzan; Tatyantoro Andrasto; Mario Norman Syah (TIN: Terapan Informatika Nusantara, 2026)
Warehouse management for packaged beverage products faces critical risks of expired products and human error in stock rotation. This research implements an IoT-based Automated Storage and Retrieval System (ASRS) integrating three stock rotation algorithms, FIFO, FEFO, and LIFO, in a single backend control platform using PHP, MySQL, ESP32 microcontroller, and QR Code scanner. Research and Development (R&D) method with Waterfall model was employed. Testing was conducted at the Electrical Engineering Laboratory of Semarang State University using 100 ml UHT milk products across 60 trials (20 per algorithm). Results show all three algorithms achieved 100% accuracy, and QR Code identification yielded 93.3% accuracy with an average response time of 287 ms. Edge case testing proved deterministic handling of identical expiry dates, simultaneous timestamps, empty stock, and full slots. FEFO proved most suitable for packaged beverage management by consistently prioritizing products with the nearest expiry date, minimizing spoilage risk. The main contributions of this research simultaneous integration of three stock rotation algorithms (FIFO, FEFO, LIFO) within a single IoT-based backend control platform, a deterministic SQL-based tiebreaker mechanism to eliminate ambiguity in identical-data conditions, and empirical validation of FEFO's superiority over FIFO and LIFO for packaged beverage products through comparative residual stock analysis.